PENGARUH PELAKSANAAN MUTASI PEGAWAI DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA - Mahendra, Novian Doni (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2015)
The objectives of this research are to investigate : (1) the significant effect of implementation of personnel transfers on the job satisfaction in PT Deltomed Laboratories Wonogiri; (2) the significant effect of job characteristics on the job satisfaction in PT Deltomed Laboratories Wonogiri; (3) the significant effect of implementation of personnel transfers and job characteristics on the job satisfaction in PT Deltomed Laboratories Wonogiri. This research used the survey quantitative research method. This research used the survey quantitative research method. Its population was all functional employees of PT Deltomed Laboratories on Wonogiri as many as 115 persons. The samples of the research consisted of 53 persons. They were taken by using the proportionate random sampling technique. The result of this research shows that implementation of personnel transfers and job characteristics simultaneously affect on the job satisfaction. Implementation of personnel transfers has a positive effect toward the job satisfaction. So that, a good implementation of personnel transfers will lead to increasing job satisfaction. It happens also in job characteristics which gives positive effect on job satisfaction, so improvement of job characteristics will lead to high job satisfaction.